Method for judging uniformity of aluminum element in titanium-aluminum alloy

By conducting full-section test piece heat treatment and tissue observation on titanium-aluminum alloy blanks, the problems of large errors in the uniformity detection of aluminum elements and long periods in the prior art are solved, and fast and accurate uniformity judgment and high visual inspection results are achieved. Meets the accuracy requirements of high-temperature thermal mechanical treatment.

CN119470427APending Publication Date: 2025-02-18AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734589.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the detection error of aluminum elements in titanium aluminum alloys is large, the detection period is long, and the true uniformity of chemical components in the entire sample or material cannot be accurately reflected, and the degree of visualization of the detection results is not high.

Method used

By taking a full-section test piece from the titanium-aluminum alloy blank, initial heat treatment and tissue morphology observation, the uniformity of aluminum elements is judged based on the grain type and grain size. The specific steps include: initial heat treatment on the test piece, air-cooling after insulation; quantitatively judging the uniformity of aluminum through tissue observation based on the linear relationship between aluminum element content and α phase change point.

Benefits of technology

It realizes rapid and accurate judgment of the uniformity of aluminum elements in titanium-aluminum alloy, shortens the detection cycle, improves the visualization of the detection results, and controls the error within 0.25 at.%, satisfying the thermal machinery in the near-α/α phase zone. Temperature accuracy requirements for processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470427A_ABST
    Figure CN119470427A_ABST
Patent Text Reader

Abstract

The invention relates to a method for judging the uniformity of an aluminum element in a titanium-aluminum alloy, belongs to the technical field of metal materials, and solves the problems of large test error, relatively long detection period, low position reduction degree and weak visualization degree in the prior art. According to the aluminum element uniformity judgment method, the test piece is subjected to initial heat treatment at the preset alpha phase transformation point temperature, and then the test piece subjected to heat treatment is subjected to structure observation, so that the phase transformation behaviors of regions with different aluminum contents in the test piece can be observed. And according to a structure observation result, heat treatment is performed every time when the initial heat treatment temperature is increased or reduced by 5-10 DEG C so as to reach the temperature of the alpha phase transformation point at each position, so that the uniformity of the aluminum element in the test piece is judged. According to the method, the test error can be controlled within 0.25 at.%, and the control requirement of the titanium-aluminum alloy near alpha / alpha phase region thermal mechanical treatment process on the temperature precision is met. And the method has the characteristics of high operability, short detection period, high position restoration degree, high visibility and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, and in particular to a method for determining the uniformity of aluminum elements in a titanium-aluminum alloy. Background Art

[0002] Titanium aluminum alloy has important applications in aerospace engines and other fields due to its excellent performance, especially in the long-term use temperature range of 650℃~850℃. Titanium aluminum alloy is usually prepared by vacuum consumable melting method, in which the aluminum content exceeds 40%. The unevenness of aluminum content will affect the mechanical properties, and this unevenness will not be eliminated in subsequent processing.

[0003] The temperature of traditional two-phase processing or heat treatment is about 50℃ below the phase transition point, and the small difference in Al element content has little effect on the structure after thermomechanical treatment; however, the near α / α phase region heat processing or heat treatment process is a heat process that heats the titanium aluminum alloy material to near the phase transition point. The influence of Al element content can be easily amplified, which will bring about significant differences in the structure after thermomechanical treatment and cause differences in the mechanical properties of the material. Therefore, before near α / α phase region thermomechanical treatment, it is very important to test the uniformity of Al element in titanium aluminum alloy billets (including ingots or bars, etc.), so as to judge whether the billet can be subjected to near α / α phase region thermomechanical treatment based on the test results and process requirements.

[0004] The traditional test of Al element uniformity of titanium aluminum alloy billets is to take samples from different positions of the billet for component detection, which can reflect the uniformity of chemical composition to a certain extent. However, this method has large errors and cannot meet the temperature accuracy control requirements of the near α / α phase thermomechanical treatment process. In addition, the detection cycle is long and the test results cannot accurately reflect the true uniformity of the chemical composition in the entire sample or material; the visualization of the test results is not high. Summary of the invention

[0005] In view of the above analysis, the embodiment of the present invention aims to provide a method for determining the uniformity of aluminum elements in titanium aluminum alloys, so as to solve at least one of the following problems: (1) in the prior art, the chemical composition uniformity test results have large errors; (2) the detection cycle is long; (3) the detection results cannot accurately reflect the true uniformity of the chemical composition in the entire sample or material; (4) the visualization of the detection results is not high.

[0006] The embodiment of the present invention provides a method for preparing a uniform titanium aluminum alloy, comprising the following steps:

[0007] S1. Take a full-section test piece from the titanium-aluminum alloy billet;

[0008] S2, perform initial heat treatment on the test piece, keep it warm for a period of time and then air cool it; the initial pretreatment temperature Tα satisfies: Tα=(20m+400)℃;

[0009] Wherein m is a known quantity, which is the content of aluminum element in the titanium aluminum alloy, in atomic percentage;

[0010] S3. Observe the microstructure of the test piece after the heat treatment in S2, and determine the uniformity of the aluminum element in the titanium-aluminum alloy billet according to the type and size of the grains.

[0011] Furthermore, in S3, if more than 98% of the grains are equiaxed grains and the difference between the upper and lower limits of the grain size is within ±30%, then the difference in aluminum content is <0.25 at.%, and it is determined that the aluminum element in the titanium aluminum alloy billet is uniform.

[0012] Furthermore, in S3, if the equiaxed grain content is less than 98% and there is a local banded structure, then S3 further includes:

[0013] The specimen is heat treated for the Nth time until the local strip-like structure disappears completely, N is an integer and N ≥ 1, and the temperature of the Nth heat treatment is T N satisfy:

[0014] T N =Tα+5*N;

[0015] The difference in aluminum content is determined to be N*0.25at.%.

[0016] Furthermore, if more than 98% of the grains are equiaxed, but the difference between the upper and lower limits of the grain size exceeds ±30%, a new full-section test piece is replaced for initial heat treatment. The initial heat treatment temperature Tα of the new cross-section test piece is NEW satisfy:

[0017] Tα NEW =Tα-5;

[0018] Furthermore, if the content of equiaxed grains in the new specimen is <98% and there is a local banded structure, the difference in aluminum content is judged to be 0.25 at.%;

[0019] If more than 98% of the new test piece is equiaxed grains and no banded structure appears, replace it with a new test piece for initial heat treatment. The initial heat treatment temperature Tα of the new cross-section test piece is NEW’ satisfy:

[0020] Tα NEW’ =Tα NEW -5;

[0021] Repeat the above steps until strip-like tissue appears locally;

[0022] The difference in aluminum content satisfies: W*0.25at.%, where W is the number of times the test piece is replaced with a new one.

[0023] Furthermore, the titanium-aluminum alloy is a two-phase titanium-aluminum alloy.

[0024] Furthermore, the thickness of the test piece is 5 mm to 10 mm; and the number of the test pieces is ≥2.

[0025] Furthermore, in S1, the test piece is selected from the target area of ​​the titanium-aluminum alloy bar or forging after blanking as needed, and the test piece is obtained by full-section cutting.

[0026] Furthermore, if the length of the rod is less than 200 mm, one test piece is taken from each end of the rod; if the length of the rod is greater than 200 mm, one test piece is taken for every additional 200 mm of the rod.

[0027] Furthermore, in S3, when observing the microstructure, when the grain size is greater than 0.2 mm, it is observed with the naked eye or an optical microscope, and a camera takes a photo; when the grain size is less than 0.2 mm, it is observed through a metallographic microscope or an electron microscope.

[0028] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0029] 1) The traditional method is to perform complex pre-treatment on the sample, analyze it with the help of instruments, etc., obtain the concentration, and then calculate the concentration difference to judge the uniformity. The present invention changes the idea of ​​the traditional method and proposes a new method for judging uniformity. Based on the special relationship between aluminum content and α phase transition point, the uniformity of aluminum is quantitatively judged by observing the structure at the corresponding α phase transition point. This new method can promote technological innovation and provide reference and reference for the detection of other materials.

[0030] 2) The prior art usually adopts multi-point sampling analysis to judge the uniformity of aluminum elements. The present invention adopts whole-section sampling analysis, from point to surface, which can more comprehensively reflect the uniformity of aluminum elements in the whole sample and can make quantitative judgments. The test error is only within 0.25at.%, which can meet the temperature accuracy control requirements of the thermomechanical treatment process in the near α / α phase region of the ingot.

[0031] 3) The existing technology involves complex sample preparation, analytical method limitations, instrument analysis time, data processing and result verification, and waiting for instrument availability, etc., and the detection cycle is long. The method of the present invention can quickly and accurately see the distribution of aluminum elements in titanium aluminum alloys, shortening the detection cycle.

[0032] 4) The existing technology for uniformity detection obtains numerical results, and the visualization of the detection results is not high. The method of the present invention obtains a picture result, which can intuitively reflect the distribution of aluminum elements at all positions in the area of ​​interest, and has a high degree of visualization.

[0033] 5) The present invention establishes a linear relationship between the aluminum content and the α phase transition point for a certain system of titanium aluminum alloy. Through this linear relationship, the temperature of α processing or heat treatment can be accurately proposed, thereby giving full play to the high temperature performance advantages of titanium aluminum alloy.

[0034] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0036] Figure 1 This is a microstructure photo of the cross section of the 46Al-1# bar after being treated at 1320°C in Example 1;

[0037] Figure 2 This is a microstructure photo of the cross section of the 46Al-2# rod in Example 2 after being treated at 1320°C;

[0038] Figure 3 This is a microstructure photograph of the cross section of the 46Al-2# rod in Example 2 after being treated at 1325℃. DETAILED DESCRIPTION

[0039] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0040] The present invention is mainly aimed at testing the uniformity of Al element in titanium aluminum alloy billet before near α / α phase region thermomechanical treatment, so as to judge whether the billet can be subjected to near α / α phase region thermomechanical treatment according to the test results and process requirements.

[0041] The uniformity of aluminum has an important influence on the performance of titanium aluminum alloy. On the one hand, the aluminum content directly affects the performance of titanium aluminum alloy parts, and the difference in aluminum content will cause the dispersion of mechanical properties; on the other hand, the difference in aluminum in the ingot is usually not eliminated by the hot working process or heat treatment process, and will always be inherited to the final component. In addition, the near α / α phase region thermomechanical treatment is to heat the titanium aluminum alloy billet to near the phase transition point, and the influence of the Al element content will be further amplified.

[0042] The present invention changes the thinking of the traditional method and proposes a new method for judging uniformity. By adjusting the temperature, different positions in the test piece reach their corresponding α phase transition points one after another. Based on the special relationship between aluminum content and α phase transition point, the uniformity of aluminum is quantitatively judged by observing the structure at the corresponding α phase transition point.

[0043] A method for determining the uniformity of aluminum elements in a titanium aluminum alloy comprises the following steps:

[0044] S1. Take a full-section test piece from the titanium-aluminum alloy billet;

[0045] S2, perform initial heat treatment on the test piece, keep it warm for a period of time and then air cool it; the initial pretreatment temperature Tα satisfies: Tα=(20m+400)℃;

[0046] Wherein m is a known quantity, which is the content of aluminum element in the titanium aluminum alloy, in atomic percentage;

[0047] S3. Observe the microstructure of the test piece after the heat treatment in S2, and determine the uniformity of the aluminum element in the titanium-aluminum alloy billet according to the type and size of the grains.

[0048] Furthermore, in S1, the titanium-aluminum alloy is a two-phase titanium-aluminum alloy, which refers to a titanium-aluminum alloy containing two phases, γ and α2. This alloy has excellent high-temperature properties and is the titanium-aluminum alloy component system with the greatest potential for application in aircraft engines.

[0049] In one embodiment, the titanium aluminum alloy has the following components in atomic percentage: Al 45-48%, Cr 1-3%, Nb 3-5%, Ta 0-1%, and the balance is titanium and unavoidable impurities.

[0050] The present invention has carried out a lot of research work on the titanium-aluminum alloy of this system, and found that the α phase transition point of the alloy is extremely sensitive to the change of the Al element content. For every 1at.% difference in Al, the phase transition point differs by 20°C. The Al element content in the alloy is extremely high, exceeding 45at.%; and other elements such as Nb, Cr, Ta, etc. have little effect on the α phase transition point of the titanium-aluminum alloy.

[0051] Finally, the present invention establishes a linear relationship between the aluminum content and the α phase transition point of the titanium aluminum alloy of this system: α phase transition point = 20m + 400, where m is the average aluminum content in the titanium aluminum alloy, expressed in atomic percentage, and the m value is in the range of 45-48.

[0052] Based on this linear relationship, it is found that different aluminum content will correspond to different α phase transition point temperatures. When the α phase transition point temperature is reached, it can be clearly observed through microstructure analysis.

[0053] This is because, when the heat treatment temperature = α phase transition temperature, the transformation between α phase and γ phase can be promoted, the banded structure of γ phase disappears completely, and the single-phase α phase grows rapidly during the heat treatment process to form equiaxed grains. After cooling to room temperature, a full lamellar structure can be obtained.

[0054] When the heat treatment temperature is greater than the α phase transformation temperature, the equiaxed grain size may become uneven due to various factors;

[0055] When the heat treatment temperature is less than the α phase transformation point, the transformation between the α phase and the γ phase is not yet complete. In addition to the equiaxed grains, there will also be a part of the γ phase banded structure.

[0056] These transformations result in significant changes in the structural organization, which can be clearly observed through microstructural analysis.

[0057] Therefore, the percentage of equiaxed grains reflects the relationship between the heat treatment temperature and the α phase transformation temperature to a certain extent. The percentage of equiaxed grains can be used to judge the uniformity.

[0058] Based on this, the present invention performs an initial heat treatment on the test piece at a preset α phase transition point temperature, and then increases or decreases the heat treatment temperature by 5°C to 10°C on the basis of the initial heat treatment temperature to reach the temperature of the α phase transition point at each position, and then judges the uniformity of the aluminum element in the test piece through the relationship between the aluminum element content and the α phase transition point and the organizational observation results of the test piece after heat treatment.

[0059] Furthermore, the thickness of the test piece is controlled within the range of 5 mm to 10 mm; and the number of the test pieces is ≥2.

[0060] Furthermore, in S1, the test piece is obtained by selecting multiple positions in the target area of ​​the titanium-aluminum alloy bar or forging after blanking as needed, and performing full-section cutting to obtain the test piece.

[0061] In one embodiment, the titanium aluminum alloy billet is a rod. If the length of the rod is less than 200 mm, one test piece is taken from each end of the rod; if the length of the rod is greater than 200 mm, one test piece is taken for every additional 200 mm of the rod.

[0062] Specifically, the aluminum element in titanium aluminum alloy often has a local uneven distribution phenomenon. The traditional chemical analysis method is to take samples from specific points of ingots or bars for component detection, which cannot fully reflect the true uniformity of the chemical composition of the entire sample or material. The determination method of the present invention determines the uniformity of the aluminum content in the area based on the morphology of the entire cross section, which can more comprehensively reflect the true uniformity of the chemical composition of the entire sample or material.

[0063] Furthermore, in S3, the uniformity determination is to observe the microstructure morphology after polishing and etching the test piece after the heat treatment in S2 to determine the uniformity of the aluminum element in the titanium aluminum alloy billet. This method obtains the result in the form of a picture, which can intuitively reflect the distribution of aluminum elements at all locations in the area of ​​interest, and has a higher degree of visualization than the numerical results of the traditional method.

[0064] Specifically, the surface of titanium aluminum alloy after heat treatment is usually rough, and it is not easy to directly observe the microstructure. Through polishing, the oxide layer and rough parts on the surface can be removed, making the surface of the sample smooth, laying the foundation for subsequent corrosion treatment and microscopic observation.

[0065] The corrosion solution used in the corrosion treatment is often a mixed solution of hydrofluoric acid, nitric acid and water, which can effectively chemically corrode the titanium aluminum alloy and expose the microstructure of the alloy.

[0066] Furthermore, in S3, when observing the microstructure, when the grain size is greater than 0.2 mm, it is observed with the naked eye or an optical microscope, and a camera takes a photo; when the grain size is less than 0.2 mm, it is observed through a metallographic microscope or an electron microscope.

[0067] Furthermore, in S3, if more than 98% of the grains are equiaxed and the difference between the upper and lower limits of the grain size is within ±30%, the difference in aluminum content is <0.25at.%, and it is determined that the aluminum element in the titanium-aluminum alloy billet is uniform, and it is determined that the billet near the test piece can undergo the next step of near-α / α phase region thermomechanical treatment.

[0068] The accuracy of heat treatment equipment depends on the specific equipment and its design purpose. The accuracy of heat treatment equipment used for phase transition point detection is usually within ±5°C. According to: α phase transition point = 20m+400, when the α phase transition point temperature control accuracy is within ±5°C, the accuracy of the aluminum content m in the aluminum alloy is within ±0.25at.%.

[0069] Further, in S3, if the content of equiaxed grains in the test piece is less than 98%, and there is a local banded structure, it means that the position of the equiaxed grains has reached its corresponding α phase transition point, but the position of the local banded structure has not reached its corresponding α phase transition point, then S3 also includes:

[0070] The specimen is heat treated for the Nth time until the local strip-like structure disappears completely, N is an integer and N ≥ 1, and the temperature of the Nth heat treatment is T N Satisfaction: T N =Tα+5*N; the difference in aluminum content is determined to be N*0.25at.%.

[0071] Specifically, if the equiaxed grain content in the test piece is less than 98% and there is a local banded structure, the test piece needs to be heat treated for the second time. The heat treatment temperature is 5°C higher than the initial heat treatment temperature T0. If the local banded structure disappears completely after treatment, it means that the phase transition point of the local banded structure has been reached. It can be judged that the aluminum content at the local banded structure is 0.25at.% higher than that at the equiaxed crystal position, that is, the difference in aluminum content is about 0.25at.%;

[0072] According to: α phase transition point = 20m + 400, it can be concluded that if the α phase transition point temperature increases by 5°C, the aluminum content m in the aluminum alloy will increase by 0.25at.%;

[0073] If the local banded structure does not completely disappear after treatment, continue to increase the temperature by 5°C for the third heat treatment, and so on. Every increase of 5°C indicates that the difference in aluminum content is 0.25at.%, until the local banded structure completely disappears. Based on this, the uniformity of aluminum elements in titanium aluminum alloy billets can be quantitatively determined.

[0074] Furthermore, in S3, if more than 98% of the test piece is equiaxed grains, but the difference between the upper and lower limits of the grain size exceeds ±30%, it means that the phase transition point at the corresponding position has been reached and the temperature of the previous initial heat treatment is too high. Then it is necessary to replace the new full-section test piece for initial heat treatment. The initial heat treatment temperature of the new cross-section test piece is Tα NEW Satisfaction: Tα NEW =Tα-5, that is, the heat treatment temperature is reduced by 5° based on the initial heat treatment temperature;

[0075] In the new test piece after heat treatment, if the equiaxed grain content is <98%, there is a local banded structure, which means that the local position has not reached the phase transition point corresponding to its concentration. The difference in aluminum content is 0.25 at.% according to the initial heat treatment temperature;

[0076] In the new test piece after heat treatment, if the equiaxed grain content is ≥98% and no banded structure appears, it means that the heat treatment temperature is still too high, and a new test piece needs to be replaced for initial heat treatment. The initial heat treatment temperature Tα of the new cross-section test piece is NEW’ Satisfaction: Tα NEW’ =Tα NEW -5, that is, lower the temperature by another 5° for heat treatment;

[0077] The above operation is repeated until a strip-like structure appears locally. For every 5°C decrease in temperature, the difference in aluminum content increases by 0.25 at.%; the difference in aluminum content satisfies: W*0.25 at.%, where W is the number of times a new test piece is replaced.

[0078] Compared with the prior art, the method for determining the uniformity of aluminum provided in this embodiment can quantitatively determine the uniformity of aluminum, control the test error of aluminum within 0.25 at.%, provide higher accuracy and reliability for determining the uniformity of aluminum, and meet the control requirements of temperature accuracy in the near α / α phase region thermomechanical treatment process of titanium aluminum alloy. It can also intuitively reflect the distribution of aluminum at all positions in the area of ​​interest, and has the characteristics of strong operability, short detection cycle, strong position restoration and visibility, etc.

[0079] The present invention is further described below with reference to the specification using examples, but the examples are only used for the present invention and are not intended to limit the present invention.

[0080] Example 1

[0081] A method for determining the uniformity of aluminum in a titanium-aluminum alloy, wherein the titanium-aluminum alloy material comprises, in atomic percentage, 46% Al, 1.8% Cr, 4% Nb, and the remainder Ti and unavoidable impurities. The rods are numbered 46Al-1#, and the uniformity of aluminum is determined for the rods. The specific steps include:

[0082] In the first step, two 5 mm thick test pieces were cut from the cross section of the bar;

[0083] In the second step, the test piece was heat treated at a temperature of 1320°C for 45 minutes, followed by air cooling.

[0084] In the third step, the test piece is polished and then corroded;

[0085] Step 4: Observe the test piece with naked eyes and a magnifying glass, and take photos with a camera. Figure 1 As shown;

[0086] The fifth step is to determine the uniformity of the aluminum element in the rod based on the observation results.

[0087] from Figure 1 It can be seen that after heat treatment, the organization is all equiaxed grains with uniform grain size, no local coarse organization or banded organization remaining. According to the correspondence between the composition, organization and heat treatment process of titanium-aluminum alloy (aluminum content), it can be judged that the aluminum element is evenly distributed in the titanium-aluminum alloy at this position.

[0088] Example 2

[0089] A method for determining the uniformity of aluminum in a titanium-aluminum alloy, wherein the titanium-aluminum alloy material comprises, in atomic percentage, 46% Al, 1.8% Cr, 4% Nb, 1% Ta, and the remainder is Ti and unavoidable impurities. The rods are numbered 46Al-2#, and the uniformity of aluminum is determined for the rods. The specific steps include:

[0090] In the first step, two 5 mm thick specimens were cut from the bar interface;

[0091] In the second step, the test piece was heat treated at a temperature of 1320°C for 45 minutes, followed by air cooling.

[0092] In the third step, the test piece is polished and then corroded;

[0093] Step 4: Observe the test piece with naked eyes and a magnifying glass, and take photos with a camera. Figure 2 As shown;

[0094] The fifth step is to determine the uniformity of the aluminum element in the rod based on the observation results.

[0095] from Figure 2 It can be seen that after heat treatment, the structure contains a large number of equiaxed grains, and some parts contain residual banded structure characteristics. The existence of banded structure indicates that there is a dual-state structure at this local position. The phase transition point at this local position is not reached at 1320℃, indicating that the aluminum content at this local position is higher than that at the equiaxed crystal position.

[0096] In order to determine the Al content in the local strip-shaped position, the test piece was subjected to a second heat treatment at a temperature of 1325°C for 45 minutes and then air-cooled. The test piece was polished and then corroded. The test piece was observed with the naked eye and a magnifying glass, and photographed with a camera. Figure 3 As shown;

[0097] from Figure 3 It can be seen that all of them are large grains, and no banded structure remains, indicating that the previous banded position has also reached the phase transition point. Usually, the Al phase difference is 1at.%, the phase transition point difference is 20°C, and the difference in aluminum in the rod is about 0.25at.%.

[0098] Example 3

[0099] A method for determining the uniformity of aluminum in a titanium-aluminum alloy, wherein the titanium-aluminum alloy material comprises, in atomic percentage, 45% Al, 1% Cr, 5% Nb, and the remainder Ti and unavoidable impurities. The rods are numbered 45Al-1#, and the uniformity of aluminum is determined for the rods. The specific steps include:

[0100] In the first step, two 5 mm thick specimens were cut from the bar interface;

[0101] In the second step, the test piece was heat treated at a temperature of 1300°C for 60 minutes, followed by air cooling.

[0102] In the third step, the test piece is polished and then corroded;

[0103] Step 4: Observe the test piece with naked eyes and a magnifying glass, and take photos with a camera;

[0104] The fifth step is to determine the uniformity of the aluminum element in the rod based on the observation results.

[0105] It can be seen with the naked eye that all of them are equiaxed crystal structures and are uniform in size. It can be judged that the difference in aluminum in the bar is less than 0.25at.%.

[0106] Example 4

[0107] A method for determining the uniformity of aluminum in a titanium-aluminum alloy, wherein the titanium-aluminum alloy material comprises, in atomic percentage, 48% Al, 3% Cr, 3% Nb, and the remainder Ti and unavoidable impurities. The rods are numbered 48Al-1#, and the uniformity of aluminum is determined for the rods. The specific steps include:

[0108] In the first step, two 5 mm thick specimens were cut from the bar interface;

[0109] In the second step, the test piece was heat treated at 1360°C for 60 min, followed by air cooling.

[0110] The third step is to polish and then corrode the test piece;

[0111] Step 4: Observe the test piece with naked eyes and a magnifying glass, and take photos with a camera;

[0112] The fifth step is to determine the uniformity of the aluminum element in the rod based on the observation results.

[0113] It can be seen with the naked eye that all of them are equiaxed crystal structures and are uniform in size. It can be judged that the difference in aluminum in the bar is less than 0.25at.%.

[0114] Comparative Example 1

[0115] A method for determining the uniformity of aluminum elements in a titanium aluminum alloy is different from Example 2 in that a chemical analysis method is used to determine the uniformity. Samples are taken at three locations, namely, the edge of the cross section of a 46Al-2# bar, half of the radius, and the center of the bar, for component detection. The detection results are shown in Table 1.

[0116] Table 1

[0117]

[0118]

[0119] According to the results in Table 1, the deviation of aluminum is 0.03%. The test results show that the uniformity of aluminum in the rod is very good. However, through Example 2, we can see that the method of the present invention intuitively shows that the difference in aluminum content has caused obvious differences in the organization of different positions of the rod. The method of the present invention determines that the difference in aluminum in the rod is about 0.25 at.%. The method of the present invention more accurately reflects the uniformity of aluminum in the rod.

[0120] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for determining the uniformity of aluminum elements in titanium aluminum alloys, characterized in that: The following steps are involved: S1. Take a full-section test piece from the titanium-aluminum alloy billet; S2, perform initial heat treatment on the test piece, keep it warm for a period of time and then air cool it; The initial pretreatment temperature Tα satisfies: Tα=(20m+400)℃; Wherein m is a known quantity, which is the content of aluminum element in the titanium aluminum alloy, in atomic percentage; S3. Observe the microstructure of the test piece after the heat treatment in S2, and determine the uniformity of the aluminum element in the titanium-aluminum alloy billet according to the type and size of the grains.

2. The determination method according to claim 1, characterized in that: In S3, if more than 98% of the grains are equiaxed grains and the difference between the upper and lower limits of the grain size is within ±30%, then the difference in aluminum content is <0.25 at.%, and it is determined that the aluminum element in the titanium aluminum alloy billet is uniform.

3. The determination method according to claim 1, characterized in that: In S3, if the equiaxed grain content is less than 98% and there is a local banded structure, then S3 also includes: The specimen is heat treated for the Nth time until the local strip-like structure disappears completely, N is an integer and N ≥ 1, and the temperature of the Nth heat treatment is T N satisfy: T N =Tα+5*N; The difference in aluminum content is determined to be N*0.25at.%.

4. The determination method according to claim 1, characterized in that: If more than 98% of the grains are equiaxed, but the difference between the upper and lower limits of the grain size exceeds ±30%, a new full-section test piece is replaced for initial heat treatment. The initial heat treatment temperature Tα of the new cross-section test piece is NEW satisfy: The NEW = Ta-5.

5. The determination method according to claim 4, characterized in that: In S3, if the equiaxed grain content is less than 98% and there is a local banded structure, the aluminum content difference is judged to be 0.25 at.%; If more than 98% of the grains are equiaxed and no banded structure is present, a new specimen is replaced for initial heat treatment. The initial heat treatment temperature Tα of the new cross-section specimen is NEW’ satisfy: The NEW’ =The NEW -5; Repeat the above steps until strip-like tissue appears locally; The difference in aluminum content satisfies: W*0.25at.%, where W is the number of times the test piece is replaced with a new one.

6. The determination method according to any one of claims 1 to 5, characterized in that: The titanium-aluminum alloy is a two-phase titanium-aluminum alloy.

7. The determination method according to any one of claims 1 to 5, characterized in that: The thickness of the test piece is 5 mm to 10 mm; the number of the test pieces is ≥2.

8. The determination method according to any one of claims 1 to 5, characterized in that: In S1, the test piece is selected from the target area of ​​the titanium-aluminum alloy bar or forging after blanking as needed, and the full-section cutting is performed to obtain the test piece.

9. The determination method according to claim 8, characterized in that: If the length of the bar is less than 200mm, take one test piece at each end of the bar; if the length of the bar is greater than 200㎜, take one more test piece for every additional 200mm of the bar.

10. The determination method according to any one of claims 1 to 5, characterized in that: In S3, when observing the organizational morphology, when the grain size is larger than 0.2 mm, it is observed with the naked eye or an optical microscope, and a camera takes a photo; when the grain size is smaller than 0.2 mm, it is observed through a metallographic microscope or an electron microscope.